Fundamental approaches to software engineering : 19th International Conference, FASE 2016, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2016, Eindhoven, the Netherlands, April 2-8, 2016. Proceedings /: 19th International Conference, FASE 2016, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2016, Eindhoven, the Netherlands, April 2-8, 2016. Proceedings. (2016) - Unknown
No abstract available